Selection of reference genes for real-time polymerase chain reaction analysis in tissues from Bombus terrestris and Bombus lucorum of different ages - Hornáková, Darina; Matousková, Petra; Kindl, Jirí; Valterová, Irena; Pichová, Iva (Analytical biochemistry, 2010)
Quantitative real-time polymerase chain reaction (PCR) is an accurate and sensitive technique for gene expression analysis. However, it requires data normalization using reference genes. Here we assessed the stability of eight reference genes in the labial gland and fat body of the bumblebees Bombus terrestris and Bombus lucorum of different ages. To date, no reference genes have been identified for these species. Our data show that arginine kinase (AK) and phospholipase A2 (PLA2) are the most stable genes in both tissues of B. terrestris. The most stable genes for the labial gland and fat body of B. lucorum were found to be elongation factor 1alpha (EEF1A) and PLA2.
Keywords: Tubulin; Animals; tukové těleso; polymerázová řetězová reakce; Fat Body; Polymerase Chain Reaction; exokrinní žlázy; ribozomální proteiny; elongační faktor 1; Exocrine Glands; Glyceraldehyde-3-Phosphate Dehydrogenases; argininkinasa; Arginine Kinase; tubulin; fosfolipasy A2; aktiny; Actins; Peptide Elongation Factor 1; Bees; Ribosomal Proteins; včely; Phospholipases A2; zvířata; glyceraldehyd-3-fosfátdehydrogenasy